Neural network based identification of hysteresis in human meridian systems - Tan, Yonghong; Dong, Ruili; Chen, Hui; He, Hong (Zielona Góra: Uniwersytet Zielonogórski)
Developing a model based digital human meridian system is one of the interesting ways of understanding and improving acupuncture treatment, safety analysis for acupuncture operation, doctor training, or treatment scheme evaluation. In accomplishing this task, how to construct a proper model to describe the behavior of human meridian systems is one of the very important issues. From experiments, it has been found that the hysteresis phenomenon occurs in the relations between stimulation input and the corresponding response of meridian systems.
Keywords: acupuncture point; hysteresis; identification; neural networks; human meridian; traditional Chinese medicine